EFEKTIVITAS SEX EDUCATION TERHADAP SIKAP IBU DALAM PEMBERIAN SEX EDUCATION ANAK USIA 4-5 TAHUN DI RAUDATUL ATHFAL BUNAYYA ISLAMIC CENTER BIN BAZ - Rahmah Widyaningrum (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2019)
Backgroud: Early childhood is a child up to 6 years old, where this age greatly determines the formation of character and personality of the children. Data from the Yogyakarta Women's and Community Empowerment Agency (BPPM) show that cases of sexual violence against children in 2016 was reached 509 cases. Cases of sexual violence on children are increasing and worrying. Therefore, it is necessary to watch out for providing sex education to children as early as possible. The role of parents is very importance in awareness of early sex education. Purpose: The purpose of this study was to evaluate the effect of sex education on the attitude of the mother in providing sex education on children aged 4-5 years in Raudatul Bunayya Islamic Center Bin Baz Karanggayam Sitimulyo Piyungan Bantul Yogyakarta. Methods: The study used pre-experimental method with one group pretest-posttest design. Fourty (40) respondents were recruited by using purposive sampling technique. Result and conclusion: Data were analyzed using Wilcoxon Signed Rank Test. In the begining, it is showed that 19 respondents (47,5%) had less good attitude. After treatment, 24 respondents (60,0%) had verry good attitude with p-value less than 0.001 (p<0.001). In conclusion, sex education can improve the attitudes of mothers in giving sex education to children aged 4-5 years in Raudatul Athfal Bunayya Islamic Center Bin Baz.